Krzywda i miłosierdzie. Charakterystyka postaci z przypowieści o dobrym Samarytaninie (Łk 10,30–37) - Krzysztof Mielcarek (The Biblical Annals, 2025)
This article provides a comprehensive analysis of the characters in the Parable of the Good Samaritan (Luke 10:30 –37). Drawing on extensive scholarly research, the author examines the traits of each character, the historical context, and interpersonal dynamics. The analysis extends beyond the parable’s characters to include participants in the theological dialogue (Jesus and the lawyer) and their audience. A careful examination of all characters reveals their interconnections. While the pair of religious elite travelers (the priest and the Levite) seems obvious, the partnership between the Samaritan and the innkeeper in aiding the victim is less apparent. Due to the sparse depiction of individual character traits by the third Evangelist, the historical background of the narrative serves as a crucial element in the characterisation process. The analysis is further enriched by considering all narrative elements and their interrelations, resulting in a nuanced portrayal of the characters.